A composer's practice. Issue 4 (1st October 2016) - Oliveros, Pauline; Krueger, Ted
ABSTRACT: Ted Krueger interviews renowned composer Pauline Oliveros about the development of the Adaptive Use Musical Instrument (AUMI) and its relationship to her history as a composer.